2009
DOI: 10.1007/s00167-009-0728-x
|View full text |Cite
|
Sign up to set email alerts
|

MRI signal changes in completely healed meniscus confirmed by second-look arthroscopy after meniscal repair with bioabsorbable arrows

Abstract: This study evaluated the MRI signal characteristics and MRI diagnostic accuracy in identifying completely healed menisci repaired with bioabsorbable arrows. A total of 34 patients (38 menisci), with a mean age of 26.0 years, underwent arthroscopic meniscal repair with bioabsorbable arrows and concomitant anterior cruciate ligament (ACL) reconstruction. Of the 34 patients, 27 were male and 7 were female. Of the 38 menisci, 27 were medial and 11 were lateral. Second-look arthroscopy was performed for each patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…When the postoperative sutured meniscus is assessed using MRI, it is difficult for conventional MRI to distinguish the healing process from retear, when high intensity change exists at the repair site . The data of this study suggest that T 1 rho mapping would be useful for evaluating the healing process of injured menisci.…”
Section: Discussionmentioning
confidence: 89%
“…When the postoperative sutured meniscus is assessed using MRI, it is difficult for conventional MRI to distinguish the healing process from retear, when high intensity change exists at the repair site . The data of this study suggest that T 1 rho mapping would be useful for evaluating the healing process of injured menisci.…”
Section: Discussionmentioning
confidence: 89%
“…A significant reduction (but not disappearance) of this hypersignal occurred from three to 12 months, which suggested that the meniscal healing process lasted for at least 12 months. Miao et al [12] evaluated the MRI signal characteristics and MRI diagnostic accuracy in identifying completely healed repaired menisci. A second look arthroscopy confirmed complete healing.…”
Section: Meniscal Repair and Mrimentioning
confidence: 99%
“…Conventional MRI is an accurate method for diagnosing meniscal derangements but it is less reliable in the postoperative assessment of meniscal repairs in the short to mid-term [9,10], particularly as a scar in a properly healed meniscus can mimic the signal seen in meniscal tears [11,12]. Hoffelner and al.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-substance degeneration could be seen in the normal menisci of older patients, so it could be difficult to distinguish from normal findings. Finally, MRI could not be employed for the dynamic evaluation of meniscal allografts utilizing range of motion [21,31,32]. Therefore, this study intended to report the need and role of second-look arthroscopy as an objective evaluation method after MAT.…”
Section: Discussionmentioning
confidence: 98%